The Effect of Artificial Intelligence on Productivity and Employment, Literature Review Study - Rifki Ambari Duila (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
Artificial Intelligence (AI) is predicted to significantly change the world of work and economic productivity. This research aims to analyze the influence of AI on productivity and employment based on a literature review. The research method was carried out qualitatively by collecting 10 indexed international and national journals related to the topic of AI and its impact on the field of work economics. The results of the article review show that the application of AI provides opportunities to increase productivity through automation of processes that were previously manual. However, the widespread adoption of AI has the potential to threaten mid- and low-level employment. Appropriate regulations are needed so that the benefits of AI can be enjoyed by the wider community, while the risk of unemployment can be minimized. The government's role is also important in providing training programs to improve human resource skills. Future research needs to consider empirical data and the specific context of a country/industry to comprehensively understand the impact of AI.